Building Resilient Workforce in a Challenging World: The Way Forward - Shukran Abd Rahman (UM Purwokerto Press, 2021)
The field of Psychology which studies human in various contexts has pertinent roles in addressing the changes that people have to deal with during the COVID19 Pandemic. Psychology researchers and practitioners in the world over have played their roles in empowering individuals and community to build new normal lifestyle during and beyond the pandemic time. The objective of this paper is to discuss the role of Psychology in empowering individuals and community to relate to increasingly challenging world. It discusses the psychosocial issues in this challenging time that warrant attention by psychologists. The paper also highlights the importance of informed interventions in empowering individuals and community to become fully functioning workforce in changing and challenging world.